Nutritional modifications to ameliorate stress hyperglycemia in critically ill patients: a systematic review - Fatemeh Rahimpour; Malihe Nejati; Shadi Farsaei; Azadeh Moghaddas; Awat Feizi (SpringerOpen, 2024)
Abstract Background and aims Appropriate nutritional support in critical care may favorably influence outcomes by attenuating the detrimental effects of hyperglycemia associated with the critical illness. This systematic review aims to present and evaluate different nutritional interventions to balance risks and rewards for critically ill patients. Methods In this systematic review, we searched online databases for several variations of terms related to critically ill patients with stress-hyperglycemia (participants), nutrition modalities (intervention), glycemic control (outcomes), and randomized controlled trials (study design) between the inception of the databases and October 2023. Results The literature search and manual searching provided 2589 articles. After removing the duplicates and excluding studies based on their abstracts or full-text assessment, 37 studies were identified as eligible for inclusion. The heterogeneous nature of these investigations precluded us from pooling data and performing meta-analysis to draw robust conclusions based on statistical analyses. The literature review in this area reveals two general perspectives for achieving this goal: optimizing various aspects of providing macronutrient support and nutritional supplementation. Conclusions The optimal approach to feeding critically ill patients remains unresolved despite numerous randomized controlled trials. Individual patient characteristics significantly influence optimal nutritional management. However, some general recommendations convey benefits for patients in the intensive care unit (ICU). Early and continuous enteral nutrition is the usual method of providing nutritional support in practice. Hypocaloric feeding and reducing carbohydrate intake are effective methods for managing SIH; however, they should be tailored to each patient's clinical characteristics. Supplementation with certain nutrients shows promise in specific groups, but more research is needed. Overall, personalized approaches based on ongoing research are the best we have now. Future studies will hopefully refine treatments and improve outcomes for these patients.